A RESOLUTION OF THE CHEMOTACTIC WAVE PARADOX - Hofer, T; Maini, P; Sherratt, J; Chaplain, M; Chauvet, P; Metevier, D; Montes, P; Murray, J (1994)
We propose an extension of the standard model for cell chemotaxis which explicitly accounts for the adaptation of the chemotactic response. We show that this model resolves the "chemotactic wave paradox" of slime mould aggregation in a natural way. © 1994.